Unveiling The Potential of Culinary Msme's in Batam Through Precision Training Need Analysis - Ulfah, Mutia; Oktarici, Eddo Nanda; Devano, Alrido Martha; Lawita, Nadia Fathurrahmi; Putri, Ancala Laras; Sabrina, Nova; Nurhasanah, Siti; van Vasten, Muhammad Barat; Sarah, May; Rahmadhani, Alyssia; Elsa, Fransiska (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This research aims to design an effective and targeted training program to uncover the skill and knowledge needs of Culinary SMEs in Batam City. The study adopts a qualitative descriptive research approach, with Culinary SMEs in Batam City serving as the informants. The research was conducted from August to November 2023, involving Bizhub Polibatam, Faculty Members, and Project Based Learning students from Department of Business Management. The research findings will be utilized as a reference by Bizhub Polibatam in developing relevant training programs to enhance the competitiveness of Culinary SMEs in Batam, thereby contributing positively to local economic growth. The pressing training needs identified for Culinary SMEs in Batam include Marketing and Digitalization Training, as well as Financial Management, preferably conducted in-person through seminars or workshops with a duration of 1-3 days.